The Effect of Cutting Type; Soil Type and Growth Regulator IBA on the Rooting of Softwood and Hardwood Cuttings of Spring and Winter in Native Atriplex halimus L. - Sharash, Omar; Alaib, Mohamad Adrawi (Al-Mukhtar Journal of Sciences, 2003)
In this study softwood and hardwood cuttings, collected from wild shrubs of Atriplex halimus. Treatd with rapid diping in solution of different concentrations (0, 1000, 3000, 5000 ppm) of Indole butyric acid (IBA), and grown in sand and soils mixture (sand and peatmoss) at five replicates, each replicate contains (10) cuttings. The obtained data were subjected to analysis of variance and results were compared by Newman Keuls test. Regarding the effect of type of cuttings on rooting, the results showed that percentage of rooted cuttings from softwood collected in spring and winter higher than that of hardwood cuttings collected in the same seasons.Results showed that, there were no significant effects of the soil type on the percentage of rooting in spring and winter softwood cuttings. Hardwood cuttings collected in spring however, shown to favour mixed soil. On the other hand soil type had no effect on rooting of winter hardwood cuttings. Results also revealed that IBA had no effect on rooting of all type of cuttings but had significant effect on the size of root system in softwood cuttings only.